Fundamental models of structural stability (Rudarsko-geološko-naftni zbornik, 2017)
In this paper, basic structural stability phenomena are described. After some general comments about stability in the fi eld of civil engineering, four elementary sources of nonlinearity are mentioned: of equilibrium equations, strain (geometry) relations, material (stress-strain) law, force and displacement boundary conditions. Four fundamental stability models are analysed, both ideal (perfect) and with geometric imperfection. Besides geometrically exact theory, initial post-buckling behaviour and linearization are briefl y sketched. This paper is concluded with comments about the infl uence of plasticity.